Characterization and electrochemical performance of CeO2 and Eu-doped CeO2 films as a manganese redox flow battery component - Rodrigues, Monica A.; Catto, Ariadne C. [UNESP]; Longo, Elson; Nossol, Edson; Lima, Renata C. (Elsevier B.V., 2018)
Hexagonal CeO2 and Eu-doped CeO2 nanoparticles were obtained using a facile microwave-hydrothermal method under mild conditions and their application towards manganese redox flow battery component were studied. The structural properties were studied by X-ray diffraction and indicate that samples present a fluorite structure. Raman spectroscopy shows Eu3+ ions substitute Ce4+ and generate oxygen vacancies. Electrochemical properties of pure and Eu-doped CeO2 films deposited at graphite substrates investigated by cyclic voltammetry and galvanostatic charge-discharge indicate that dopant concentration affects the electrochemical properties of CeO2. The increase in the reversibility redox of electrochemical systems observed is attributed to coexistence of Ce4+/Ce3+ redox couple confirmed by XPS. Charge-discharge tests display coulombic and voltage efficiency values of above 80% and 90%, respectively. The obtained specific capacity for Ce0.99Eu0.01O2 (372.49 mAh/g) and pure oxide (334.84 mAh/g) indicates that both samples are promising for application in Mn-batteries. (C) 2018 Published by Elsevier B.V. on behalf of Chinese Society of Rare Earths.
Keywords: Cerium oxide; Europium; Nanoparticles; Electrochemical properties; Batteries; Rare earths